Os músicos, por eles mesmos: criativos, hiperflexíveis e “à deriva” - Moya, Cyntia Malaguti (2024)
This project investigated musicians, considered as "creative" workers, questioning how they perceive themselves as workers and how such perceptions impact their career management. The main objective was to analyze, based on the interpretations of the subjects themselves about their own experiences, how careers are built in an activity perceived as relying more on talent than formal education, placing the discussion in the context of work reconfigurations in recent decades. To this end, we sought to recover the logic that articulates "creativity," flexible markets, and the use of new technologies in the daily lives of their activities and trajectories. The hypothesis was that musicians' self-perceptions are linked to meanings attributed to musical activity, which manifest in heterogeneous forms of "being an artist," blending work, personal fulfillment projects, and various activities within and outside of music, depending on whether it is understood as a primary or complementary occupation. The scope of the analysis was the state of São Paulo (SP) and the period between 2012 and 2023. The approach was qualitative, involving the application of semi-structured interviews and field observations. The doctoral research, conducted between the years 2020 and 2024, also followed the context of social isolation due to the pandemic. Complementing the proposal, we discussed throughout the text and in a specific chapter how the pandemic affected a traditionally restricted market situation. The results showed that most musicians identify as entrepreneurs, associating this self-image with positive meanings. Additionally, they value personality traits such as a taste for change and the ability to restart and constantly reinvent themselves to cope with instability and uninterrupted work, which requires high emotional engagement and the performance of multiple activities. Thus, this research aims to contribute to discussions on the complexity of contemporary work, addressing the intersections between professionalization and amateurism, work and personal life, and the meanings attributed to hyper-flexible work contexts.